Dismissal of judges for unexcusable error and their impact on rights - constitutional guarantees - María Yokir Reyna Zambrano (Iustitia Socialis, 2019)
The article is an advance of an institutional research project, which aims to analyze the administrative dismissal of judges in the Ecuadorian State for inexcusable error and its impact on constitutional rights and guarantees, 2011-2017 period, using a documentary methodology - bibliographic, which allows to present an analytical advance of a research work in development, having as a population sample, documents, laws, research, inherent to the topic raised. It is concluded that the affectations are numerous, such as those made to citizens when they go to justice, the State of Rights, the Judicial Career and the rights of the judge as a public official.